Evaluation of the pregnant women's approaches regarding drug utilization - AKICI, AHMET; GÖREN, MEHMET ZAFER (KARE PUBL, 2020)
OBJECTIVE: Drug utilization habits of the pregnant are a critical aspect of rational use of the medicine (RUM). This study aimed to analyze the RUM related attitudes and the behaviors of women during their pregnancies. METHODS: The data were collected between May 2016-October 2016 by conducting surveys to 71 pregnant women admitted to the private and governmental hospitals in five districts of Northern Cyprus. The sociodemographic characteristics of the pregnant as well as their attitudes and behaviors concerning drug use were evaluated. RESULTS: The mean age and the gestational week of the patients was 29.7 +/- 4.3 years and 25.7 +/- 11.2 weeks, respectively. Planned pregnancies constituted 71.8% of all. The percentage of patients with an unplanned pregnancies who were using drugs at the time of the survey (25.0%) was lower than that in those with planned pregnancies (49.0%, p<0.05). Almost two-thirds (66.2%) of the women were exposed to a drug during pregnancy, mostly for vitamin/mineral prophylaxis (38.3%) and agents controlling nausea/vomiting (19.1%). Two out of eleven women (18.2%) were using folic acid when they learned about their pregnancy. One of the drugs used for the chronic disorder in the third trimester was acetylsalicylic acid (11.1%), a category D drug in this setting. Most of the patients stated that they frequently read the instructions (60.9%), often paying attention to side effects (56.5%). Considering some of the habits related to drug use, 8.7% and 10.9% of pregnant women declared that they sometimes did not follow the instructions and dosage/duration of the drug usage, respectively. Seven patients (15.2%) declared that they did not consider side effects on the medication guide while more than half (56.5%) did it often. Near one in five (19.6%) of the pregnant women stated that they hesitated about the drug usage due to teratogenicity risks. CONCLUSION: Our study highlights the drug utilization attitudes and behaviors of pregnant women during pregnancy in Northern Cyprus, indicating several shortcomings, including insufficient prenatal folic acid use, occasional use of risky drugs, and unsatisfactory medication guide handling. Available findings underline the necessity of education not only for patients but also for healthcare providers to disseminate RUM in pregnancy.
Keywords: Drug use; first visit; planned; pregnancy; teratogenicity; OVER-THE-COUNTER; UNPLANNED PREGNANCY; ACID SUPPLEMENTATION; HERBAL REMEDIES; MEDICATION USE; FOLIC-ACID; PRESCRIPTION; HEALTH; PREVENTION; ATTITUDES